Epistemic Isomorphism in Response to the Argument from Error - Laera, Rodrigo (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The aim of this paper is to present a reply to the argument from the error based on the epistemic isomorphism, where the explanatory structure that constitutes our beliefs is similar in the case that we live in the real world as in the case we are, by example, brains in a vat. In the first part, the problems that arise from the argument from error are exposed (par., 2-4), while, in a second part (par., 5 and 6), this argument is modified so that it can be avoided the above problems and the isomorphic response is exposed. Finally, it is concluded that, given the isomorphism, to opt for the possibility of the real world or the skeptical possibility has no epistemic relevance.